Efektivitas Program Talk Show “Mama dan Aa” (Studi Kasus di Prancak Dukuh, Panggungharjo, Sewon, Bantul, Yogyakarta) - Siti Maemunah (Rekam: Jurnal Fotografi, Televisi, Animasi)
This research is reasonable to be done, in order to trace about the effectivity of a talk show program “Mama dan Aa” in Indosiar television station, that has been running through more than 3 years, with national scale broadcasting. This talk show contents of Islamic speech, consist of Qur’an way of thinking, even consists of legacy regulation in Islamic perspective, marriage problem, and society problem as well.Although this research relates to a content of a program in mass media with Islamic perspective, as a teaching staff in the faculty of Recorded Media Art which based on artistic, the researcher decreases some indicators in making questions that relate to the artistic aspect. A reality talk show that used television media, think about interior with all aspects, along with color composition with its harmony.Indeed lyrict and music are the important aspects of Talk Show program. That could be analized.From this research, 90 respondents confess that the material in Talk Swowprogram “Mama dan Aa”, influence them in their daily life, and they intend to apply those materials to their lives, 85 % feel regret when they do not apply them in their real lives. 95 % are found, get their knowledges about religion through listening to the speech on television or directly accept it from the mosque, in this research locates at the mosque in Prancak dukuh which give them peasful for their souls.